Knowledge Management in the Association of the Aviation Industry Entrepreneurs Group "Aviation Valley" - Marcin KŁAK (Communications of International Proceedings, 2021)
The main purpose of this study is to present the concept of knowledge management in the companies of the Association of the Aviation Industry Entrepreneurs Group "Aviation Valley". The paper presents how the concept of knowledge management is implemented in contemporary high-tech enterprises and how it helps to build a competitive advantage. It was also pointed out that the most important factors determining the competitiveness of companies (apart from price, product quality, financial potential of the company, contacts and business partners, quality of the business support environment) include not only technological advancement of a given business entity (investments in fixed assets and research and development activities) but also knowledge and qualifications of employees and the use of know-how.
Keywords: Knowledge management; Aviation Valley; modern enterprise; industrial cluster